Scattered : the forced relocation of Poland's Ukrainians after World War II - Reilly, Diana Howansky (The University of Wisconsin Press, 2013)
In this book, the author uses true accounts of her family's history to discuss the treatment of Ukrainian citizens of Poland after World War II and the political upheaval and relocation which occurred during this era.